2023
DOI: 10.1038/s41598-023-36474-w
|View full text |Cite
|
Sign up to set email alerts
|

Temperature contributes to host specialization of coffee wilt disease (Fusarium xylarioides) on arabica and robusta coffee crops

Abstract: Coffee wilt disease, caused by the fungus Fusarium xylarioides, is a vascular wilt disease that has affected coffee production in sub-Saharan Africa over the past century. Today, the disease has two host-specific populations specialising on arabica and robusta coffee crops, which grow at high and low altitude, respectively. Here we test whether adaptation to different temperatures contributes to specialisation of the fungi on each crop. Firstly, climate models show that the severity of the arabica and robusta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…While farmers did not agree on whether or not coffee wilt disease increased (i.e., there were equal numbers of farmers who perceived a decrease or increase), meteorological data supported farmers who linked an increase in coffee wilt disease with rising annual temperatures. A positive relationship between temperature and coffee leaf rust and coffee wilt disease matches previous studies (Adugna et al, 2008;Avelino et al, 2012;Gagliardi et al, 2020;Zhang et al, 2023), and the mechanisms are likely that temperature increases pathogen development rate, is harmful to host physiology, and decreases host resistance (Elad & Pertot, 2014;Pautasso et al, 2012). While farmers did not agree on whether or not coffee yield increased, meteorological data supported those farmers who perceived a decrease in coffee yield due to an increase in mean annual temperature and temperature during flowering.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…While farmers did not agree on whether or not coffee wilt disease increased (i.e., there were equal numbers of farmers who perceived a decrease or increase), meteorological data supported farmers who linked an increase in coffee wilt disease with rising annual temperatures. A positive relationship between temperature and coffee leaf rust and coffee wilt disease matches previous studies (Adugna et al, 2008;Avelino et al, 2012;Gagliardi et al, 2020;Zhang et al, 2023), and the mechanisms are likely that temperature increases pathogen development rate, is harmful to host physiology, and decreases host resistance (Elad & Pertot, 2014;Pautasso et al, 2012). While farmers did not agree on whether or not coffee yield increased, meteorological data supported those farmers who perceived a decrease in coffee yield due to an increase in mean annual temperature and temperature during flowering.…”
Section: Discussionsupporting
confidence: 84%
“…As a result, food insecurity and migration increased throughout Central America, particularly among smallholder coffee farmers (Bacon et al, 2017;Dupre et al, 2022). Another example is the coffee wilt disease Fusarium xylarioides, which strongly affects coffee production in Africa and has become more severe with increasing temperatures (Flood, 2022;Zhang et al, 2023). To mitigate the negative effects of climate change, we need to be able to predict changes in disease dynamics and yield, for which we can use relationships obtained from long-term time series of climate, disease levels, and yield.…”
mentioning
confidence: 99%
“…The disease was regarded as a minor one but suddenly gained major status possibly due to changes in climate, management practicespractices or virulenvce of the pathogens. According to Zhang et al [20], changes in key climate variables such as temperature and moisture influence disease infectivity and pathogenicity. For instance, studies have shown that temperature significantly impacts growth and reproduction of Fusarium species [20].…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhang et al [20], changes in key climate variables such as temperature and moisture influence disease infectivity and pathogenicity. For instance, studies have shown that temperature significantly impacts growth and reproduction of Fusarium species [20]. According to Fick and Hijmans [21] the temperature levels are increasing and will increase by 2 to 6 • C in coffee-growing regions of Africa by 2080, and this will potentially facilitate the occurrence and spread of Fusarium bark disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing temperature has an impact on increasing length, fruit diameter, and number of fruit and time of appearance of the first fruit (Rinaldi, 2022). In the other hand, altitude also affect the growth of the coffe desease like wilt by Fusarium xylaroides (Zhang et al, 2023). Change of temperature e not only afect growth and production of crop plants directly (Tubiello et al, 2007) but also, indirectly, by infuencing the infectivity and pathogenicity of crop diseases (Newbery et al, 2016).…”
Section: Introductionmentioning
confidence: 99%